Model Integrasi Mathematics to Explore Al-Quran: Sebuah Studi Literatur Sistematik - Muhammad Zia Alghar; Anisatur Rizqiyah (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to systematically review various literatures that use the mathematics to explore Al-Quran integration model. A qualitative approach with the type of systematic literature study was used in this research. The data used were 17 articles related to research that used the mathematics to explore Al-Quran integration model from 2014-2024. Data was collected through google scholar database and publish or perish application. Data analysis was done by identifying, selecting, reviewing, comparing, and interpreting the data. The results showed that there are various studies that use the integration model of mathematics to explore Al-Quran which can be grouped based on the year of research, researcher productivity, type of publication, and mathematical concepts contained. This research is useful for teachers, lecturers, and academics in providing references related to various studies that use the mathematics to explore Al-Quran integration model.